A mechanically stable laser diode speckle interferometer for surface contouring and displacement measurement - Francis, Daniel; Masiyano, Dackson; Hodgkinson, Jane; Tatam, Ralph P. (Institute of Physics (IOP), 2015)
Electronic speckle pattern interferometry (ESPI) is demonstrated using a simple configuration consisting of a wedged window and a beamsplitter. The window serves to produce a reference beam which is in-line with the scattered object beam. The system is almost common-path and therefore provides much better mechanical stability than conventional ESPI configurations, which have widely separated beam paths. The configuration has collinear observation and illumination directions and therefore has maximum sensitivity to out-of-plane displacement. Wavelength modulation through adjustment of the laser diode control current provides a convenient method of phase shifting without the need for external moving parts. Further, variation of the laser diode control temperature allows extended wavelength tuning to adjacent longitudinal modes, facilitating surface contouring measurements via the two-wavelength technique. The interferometer is demonstrated for surface displacement measurement with a 3.3 μm centre displacement measured over a 15 mm × 15 mm region of a flat plate. Contour measurements of a shaped object are made using an equivalent wavelength of 1.38 mm.
Keywords: ESPI; speckle; interferometry; contouring; laser diode